REGULATORY COOPERATION ON CROSS-BORDER PERSONAL DATA FLOWS BETWEEN CHINA AND MALAYSIA: A COMPARATIVE LEGAL ANALYSIS UNDER RCEP AND CPTPP FRAMEWORKS - Shan, Deng (UI Scholars Hub, 2025)
China and Malaysia have demonstrated strong momentum in the development of their digital economy. However, the management and protection of personal data in cross-border flows have emerged as major challenges, underscoring the urgent need for enhanced regulatory cooperation to ensure data security and circulation efficiency. This study employs a qualitative research methodology, with a focus on comparative analysis and documentary research, to examine the similarities and differences in data governance rules under the frameworks of the Regional Comprehensive Economic Partnership (RCEP) and the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP). It further examines the role and challenges of these frameworks in facilitating cross-border regulatory cooperation on personal data between China and Malaysia, as well as assessing the impact of the Association of Southeast Asian Nations (ASEAN) on Malaysian legislation and China-Malaysia cross-border data regulatory cooperation within the RCEP and CPTPP frameworks. The study shows that China and Malaysia can leverage the RCEP as a mechanism for transitions and adjustments, and draw on the high-standard rules of the CPTPP to explore an innovative and inclusive cooperation model. The study proposes the idea of building a regional cross-border data governance framework, aiming to promote both cross-border management coordination of personal data between China and Malaysia, and further development of the digital economy in the two countries.